2007
DOI: 10.1016/j.humimm.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HLA-G and HLA-E Expression in Human Neuronal Cells After Rabies Virus or Herpes Virus Simplex Type 1 Infections

Abstract: Abbreviations : RABV (rabies virus), HSV-1 (herpes simplex virus type 1), mAb monoclonal antibody, HCMV ( Human cytomegalovirus) 2 Abstract HLA-G and E are non classical human MHC class I molecules. They may promote tolerance leading to virus and tumour immune escape. We recently described that the herpes simplex virus type 1 (HSV-1), a neurotropic virus inducing chronic infection and neuron latency, and rabies virus (RABV), a neuronotropic virus triggering acute neuron infection -up-regulate HLA-G expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 49 publications
2
41
0
3
Order By: Relevance
“…9 Inflammation of neuron cell bodies in the absence of directly observable pathogens in the cell body has some precedent in mammals: Human neurons express atypical MHC-I molecules in response to infection by rabies or herpesviruses, and rodent neurons in vitro can internalize and express foreign ovalbumin antigens via MHC-I complexes that leads to cytotoxic T-cell-mediated killing. 22,23 Histopathologically, most of the inflammatory cells surrounding cell bodies in zebrafish with P. neurophilia resembled microglial cells rather than T cells (Figs. 4 and 5).…”
Section: Figmentioning
confidence: 99%
“…9 Inflammation of neuron cell bodies in the absence of directly observable pathogens in the cell body has some precedent in mammals: Human neurons express atypical MHC-I molecules in response to infection by rabies or herpesviruses, and rodent neurons in vitro can internalize and express foreign ovalbumin antigens via MHC-I complexes that leads to cytotoxic T-cell-mediated killing. 22,23 Histopathologically, most of the inflammatory cells surrounding cell bodies in zebrafish with P. neurophilia resembled microglial cells rather than T cells (Figs. 4 and 5).…”
Section: Figmentioning
confidence: 99%
“…22 Although removal of the 92 bases produces a more stable mRNA, the presence of þ 14 bp has been associated with a lower mRNA production. 20 Some virus including Epstein-Barr virus, rabies virus and cytomegalovirus may upregulate HLA-G expression; 13,[23][24][25] however, the function of HPV in HLA-G expression has not been determined. Recently, we reported that cervical lesions may express HLA-G molecules that may differ according to the severity of SIL in HPV-infected women.…”
Section: -15mentioning
confidence: 99%
“…HLA-G was reported to be expressed on cells infected with rabies virus [13,14], influenza virus [15], and herpes B virus [16]. In our lab, we have shown that herpes B virus infected human cells induce increased surface expression of HLA-G but HSV-1 infected cells do not show similar HLA-G expression [16].…”
Section: Hla-gmentioning
confidence: 76%